Coexistence of trapped and flow-transported nuclei enables fast pigeon post communication across multinucleated cell - Johnny Tong; Kaspar Wachinger; Fabian K. Henn; Nico Schramma; Siyu Chen; Karen Alim (Proceedings of the National Academy of Sciences, 2025)
Multi-nucleated cells exist in all domains of life, ranging from animals, plants, and fungi to single-celled organisms such as the slime mold Physarum polycephalum . The large cell size, in the case of Physarum reaching centimeters and more, challenges the coordination of nuclei activity as signals need to cross large distances. In search of a mechanism for fast long-ranged communication among nuclei, we quantify nuclei dynamics and cytoplasmic flows in Physarum ’s tubular network. We observe nuclei in two interchangeable, dynamic states: mobile, flowing within the cytoplasmic shuttle flow, or trapped in the tube’s porous cell cortex. As we find nuclei to accumulate at the tube’s inner fluid–porous interface we theoretically explore and confirm, with physiological parameters, that slowing down of mobile nuclei during flow is sufficient for diffusible signal exchange between mobile and trapped nuclei. We analytically derive that communication akin to pigeon post with mobile nuclei serving as pigeons shuttling between trapped nuclei acting as waypoints, gives rise to signaling velocities that account for the rapid intracellular reorganization observed in Physarum . Since signal transfer by flow-transported nuclei outcompetes the mere diffusion of signals encoded in cytosolic proteins, pigeon post communication surpasses alternative signaling mechanisms, even diffusive relay signaling up to 20-fold in velocity. The key ingredients of pigeon post communication, namely alternating flows and waypoints, exist in other multi-nucleated cells and may also be generalized beyond intracellular signaling.